z⋅z=9⋅10⋅15⋅6

Multiply z by z.

z2=9⋅10⋅15⋅6

Multiply 9 by 10.

z2=90⋅15⋅6

Multiply 90 by 15.

z2=1350⋅6

Multiply 1350 by 6.

z2=8100

z2=8100

Take the square root of both sides of the equation to eliminate the exponent on the left side.

z=±8100

Simplify the right side of the equation.

Rewrite 8100 as 902.

z=±902

Pull terms out from under the radical, assuming positive real numbers.

z=±90

z=±90

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

z=90

Next, use the negative value of the ± to find the second solution.

z=-90

The complete solution is the result of both the positive and negative portions of the solution.

z=90,-90

z=90,-90

z=90,-90

Solve for z z*z=9*10*15*6